2004
DOI: 10.1149/1.1796445
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Morphology, and Dielectric Properties of Nanocomposite Oxide Films Formed by Anodizing of Sputter-Deposited Ta-Al Bilayers

Abstract: Anodizing of Ta-Al bilayers ͑aluminum deposited on tantalum͒ was performed in 0.2 M H 2 C 2 O 4 solution to transform the aluminum metal into its nanoporous oxide followed by pore widening and reanodizing to different voltages in the range of 100-600 V. The anodic films consist of an upper layer of nano-sized tantala columns penetrating into the pores and a lower layer of continuous tantalum oxide under the porous alumina film. The columns are mainly composed of tantalum pentoxide and tantalum sub-oxides TaO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 28 publications
7
66
0
Order By: Relevance
“…This may be possible because it is reported that the AAO walls are porous. 25 Once part of the AAO wall is dissolved, the diameter of the AAO pore become bigger. On …”
Section: Resultsmentioning
confidence: 99%
“…This may be possible because it is reported that the AAO walls are porous. 25 Once part of the AAO wall is dissolved, the diameter of the AAO pore become bigger. On …”
Section: Resultsmentioning
confidence: 99%
“…The first anodization was conducted in the aqueous electrolytes of 0.3 M oxalic acid under a potentiostatic mode of 40 V at 1 ºC with platinum counter electrode. The formation of tungsten oxide through the penetration into the AAO barrier layer was ascribed to the dissolution of Al-O bonds at the AAO barrier layer [6]. During the formation of AAO, the current increased with the anodization time (region i) and decreased abruptly (region ii).…”
Section: Methodsmentioning
confidence: 99%
“…Among them, tungsten oxides with amorphous or crystalline structures have been widely studied for the applications to electrochromic devices, electrochemical capacitors, and gas sensing devices [2][3][4]. Many researchers have investigated the nanostructured materials with high specific surface area for the applications to the anodic and cathodic electrodes of batteries and capacitors [5][6][7]. Many researchers have investigated the nanostructured materials with high specific surface area for the applications to the anodic and cathodic electrodes of batteries and capacitors [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The O 2 evolution has been associated with an amorphousto-crystalline transition of the bottom oxide (hereafter the 'field crystallization'), [16] the phenomenon being generally known for barrier-type anodic film growth on Ti surface at relatively low potentials of less than~15-20 V. [19][20][21] However, anodic oxides on other valve metals like Ta, Nb, or W grow generally amorphous during the barrier-type anodizing up to substantially higher potentials, [22][23][24][25] and their PAA-assisted anodizing results in long-aspect-ratio amorphous and stable nanocolumns or rods, [26][27][28][29] without obvious O 2 evolution. It is anticipated that alloying of titanium with one of these metals could suppress the field crystallization and void formation in the anodic oxide, as well as minimize the incorporation of alumina in the root composition and, therefore, improve the stability of the column arrays.…”
Section: Introductionmentioning
confidence: 99%